THE EFFECT OF INTERNAL CONTROL SYSTEM ON FINANCIAL MANAGEMENT AT BLUD PETALA BUMI HOSPITAL, RIAU PROVINCE - Arini, Arini; Zaharman, Zaharman; Novianti, Serly (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study aims to determine the effect of the internal control system on financial management at the BLUD of Petala Bumi Hospital, Riau Province. The population in this study were employees at the Petala Bumi Hospital, Riau Province, which consisted of 11 people from the Finance Section, 6 people from Casemix, 3 people from Cashier, 4 people from Planning, 6 people from Logistics and Assets. This research approach uses quantitative with primary data sources. The analytical method used is Simple Linear Regression with the help of SPSS 23. The statistical test results show that the Internal Control System has a significant effect on financial management at the BLUD of Petala Bumi Hospital, Riau Province.